Asymmetric shifts in precipitation due to urbanization across global cities - Jinghua Xiong; Yuting Yang; Long Yang; Dawen Yang (Nature Communications)
Abstract Urbanization alters precipitation patterns by modifying thermal, dynamic, and chemical processes in the atmosphere. However, its effect on precipitation regimes, particularly at the sub-daily scale, is poorly understood. In this work, we use a high-resolution, spatially continuous satellite precipitation dataset to examine urbanization-induced shifts across precipitation intensities over global cities. We show that urbanization generally causes asymmetric shifts, increasing lower-intensity events and decreasing higher-intensity ones, with distinct patterns in tropical monsoon regions. These shifts, primarily driven by changes in event frequency, lead to reduced precipitation variability in urban areas, particularly in temperate cities and those exhibiting higher urbanization levels. Sub-daily analysis reveals that lower-intensity precipitation most notably increases in the early morning, while higher-intensity events decrease in the late afternoon, dampening diurnal precipitation variability. These findings offer important observational evidence of how urbanization alters precipitation regimes and highlight the need for adaptive urban water management strategies.